2012
DOI: 10.1002/nbm.2886
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of traumatic brain injury in a rat focal contusion model

Abstract: Serial magnetic resonance imaging (MRI) facilitates the in vivo analysis of the intra- and intersubject evolution of traumatic brain injury (TBI) lesions. Despite the availability of MRI, the natural history of experimental focal contusion lesions in the controlled cortical impact (CCI) rat model has not been well described. We performed CCI on rats and MRI during the acute to chronic stages of cerebral injury to investigate the time course of changes in the brain. Female Wistar rats underwent CCI of their lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 81 publications
4
32
0
Order By: Relevance
“…When much attention has been given to the generation of disease models, the baseline characteristics of the animals used have typically been assumed to be normal in the absence of external behavioral or physical signs. The inadvertent inclusion of ventriculomegaly Wistar rats in neurological studies may contribute variability to experiments that lead to unforeseen bias in studies of low sample size (53). Beyond the implications that these ventriculomegaly rats may have for interpretation of experimental results, this newly documented form of ventriculomegaly may be importance as an animal model to study hydrocephalus/ventriculomegaly in association with cyst formation and/or vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…When much attention has been given to the generation of disease models, the baseline characteristics of the animals used have typically been assumed to be normal in the absence of external behavioral or physical signs. The inadvertent inclusion of ventriculomegaly Wistar rats in neurological studies may contribute variability to experiments that lead to unforeseen bias in studies of low sample size (53). Beyond the implications that these ventriculomegaly rats may have for interpretation of experimental results, this newly documented form of ventriculomegaly may be importance as an animal model to study hydrocephalus/ventriculomegaly in association with cyst formation and/or vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [24], a 6-mm craniotomy was followed by CCI with a 5-mm flat impactor tip over the left motor cortex (2.5 mm left lateral and 1.0 mm anterior from the bregma; velocity = 5 m/s, depth = 2.5 mm and dwell time = 100 ms). The same surgeon performed all CCI surgeries for a given cohort of rats.…”
Section: Methodsmentioning
confidence: 99%
“…Brains were imaged using a 7-T Bruker vertical bore magnet (Bruker BioSpin, Billerica, MA, USA) with a 10-mm inner diameter birdcage coil with a three-dimensional multiecho gradient echo sequence: repetition time (TR) = 200 ms, effective echo time (TE) = 17.5 ms (six echoes, 5 ms echo spacing), field of view = 3.0 × 1.5 × 1.25 cm 3 , 512 × 256 × 128 matrix, four averages and 30° flip angle as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, these investigators exposed animals to stress, and reported stress alone did not increase NSS-R scores. Using a CCI model, Turtzo et al (2013) reported significant increases in NSS-R scores at 1 and 14 days post-injury, with scores returning to baseline levels at 28 days post-injury.…”
Section: Anticipated Resultsmentioning
confidence: 88%